2018
DOI: 10.1103/physrevmaterials.2.104604
|View full text |Cite
|
Sign up to set email alerts
|

Towards bipolar tin monoxide: Revealing unexplored dopants

Abstract: The advancement of transparent electronics, one of the most anticipated technological developments for the future, is currently inhibited by a shortage of high-performance p-type semiconductors. Recent demonstration of tin monoxide as a successful transparent p-type thin-film transistor and the discovery of its potential for ambipolar doping, suggests that tin monoxide-an environmentally friendly earth-abundant material-could offer a solution to this challenge. With the aim of enhancing the electronic properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…In any case, oxides generally exhibit an important doping asymmetry and bipolar oxide semiconductors [135] represent only a small subset (e.g. CuInO 2 [136] , SnO [137] , Ga 2 O 3 [138] , Ni x Cd 1−x O 1+δ [139] , SnNb 2 O 6 [140] , ZrOS [141] ).…”
Section: Otf As Electrodes: Transparent Metalsmentioning
confidence: 99%
“…In any case, oxides generally exhibit an important doping asymmetry and bipolar oxide semiconductors [135] represent only a small subset (e.g. CuInO 2 [136] , SnO [137] , Ga 2 O 3 [138] , Ni x Cd 1−x O 1+δ [139] , SnNb 2 O 6 [140] , ZrOS [141] ).…”
Section: Otf As Electrodes: Transparent Metalsmentioning
confidence: 99%
“…15,18 These materials possess a VBM with significant contributions from anion p-states, which for nonoxide anions are more delocalized than the 2p orbitals of oxygen. 18 Materials such as sulfides, iodides, and especially phosphides 13,15,16,19,22 were found via highthroughput screening and first-principles calculations to commonly have m à h < 5 m e , with phosphides including many examples <1 m e , owing to the metal-p and phosphorous-p orbital mixing at the VBM. 15 Notable p-TCM candidates in these material classes are boron phosphide (BP), 15 copper iodide (CuI), [22][23][24] CuAlS 2 , 25,26 (Zr,Hf)OS, 16,27 and Mg:LaCuOSe.…”
Section: Computational Screening For Disperse Valence Band Materialsmentioning
confidence: 99%
“…In this review, we present an overview of the experimental techniques and synthesis approaches reported on DVMs with the aim to bridge the gap between computational and experimental works on p-TCMs. The authors note that while oxide materials with promising p-type conductivity and transparency properties have received attention in the recent computational literature, 14,19 we focus herein on materials beyond oxides, as oxides are considered well-known chemistries with several synthesis approaches already at advanced stages of development.…”
Section: Introductionmentioning
confidence: 99%
“…Besides all the above efforts, the structural and electronic properties of SnO have also been studied in the past using density functional theory (DFT). Recently, an extensive study for the most promising n-and p-type dopants has been published 20 where Li, Na, K, Cs, Rb and Ag were were found to act as shallow acceptors and therefore were proposed for p-type doping of SnO at a substitutional position, replacing Sn. Additionally, isovalent Sn 1−x M x O (M = Mg, Ca, Sr, Zn) alloys have been examined theoretically for the application of SnO as a thin film based solar cell 2 .…”
mentioning
confidence: 99%
“…Contrary to efforts on Pb doping of SnO 2 , Pb x Sn 1−x O 2 and the PbO 2 /SnO 2 heterojunction (HJ), there are very few investigations on Pb doping of SnO and the properties of the ternary oxide Pb x Sn 1−x O. Pb doping of SnO was investigated experimentally by Liao et al 16 who observed a small increase of the optical band gap by 0.7 eV (to 2.75 eV) and a decrease of the hole mobility, attributed possibly to trap formation. The preparation of SnO/ PbO solid solution and its properties were examined by Kwestroo et al 24 , whereas Lim et al 20 investigated the properties of layered SnO and layered PbO for energy applications. They concluded that SnO is a better material for electron transfer and a better catalyst for hydrogen evolution than PbO.…”
mentioning
confidence: 99%